Analisis Permasalahan Transportasi Berkelanjutan di Kota Metropolitan Surabaya : Studi Kasus Perkotaan Padat Penduduk - Novita, Dwi (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2022)
This research aims to examine the issues and solutions of sustainable transportation in the metropolitan city of Surabaya, focusing on densely populated urban areas. The research method used in this study is qualitative, relying on secondary data sources. The findings of this study reveal that one of the main factors causing transportation problems in urban areas, especially in Surabaya, is the high number of motorized vehicles leading to traffic congestion. Secondly, there is a lack of efficiency in public transportation. Thirdly, there is a lack of comfort and safety. Fourthly, there is a scarcity of facilities in public transportation, and lastly, there is a lack of awareness among the population regarding the use of traffic facilities. Then, the high rate of growth in Surabaya city will result in a significant amount of traffic congestion in certain areas. Transportation challenges with cross-regional impacts, such as in the metropolitan urban areas of Surabaya, cannot be addressed or handled separately by individual regions. To overcome these challenges, coordination and cooperation between various areas are required. In order to achieve efficiency and optimal results, it is recommended that management be carried out in an integrated manner as a single system, without considering administrative boundaries. From these issues, the researcher proposes a solution, which is the establishment of sustainable transportation such as the Mass Rapid Transit (MRT), improving facilities and infrastructure to support the transportation sector, and raising public awareness to encourage the use of public transportation.